2011
DOI: 10.1071/bt10306
|View full text |Cite
|
Sign up to set email alerts
|

Inflorescence and floral ontogeny in Jasminum fruticans (Oleaceae)

Abstract: The inflorescence and floral ontogeny of the oleaceous tropical bush, Jasminum fruticans L. were studied using epi-illumination light microscopy and compared with other Oleaceae. The flowers are arranged in a thyrsoid inflorescence with a determinate pattern of development. Deviations from the common pathway of floral ontogeny in Oleaceae observed in J. fruticans are characterised by pentamery in calyx and corolla, diagonal position of sepals, some deviation from acropetal and simultaneous initiation of floral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The floral organ numbers are determined during the initiation and fate determination of the floral organs. Scanning electron microscopic studies of the initiations of floral organs revealed that the sepal primordia initiate in sequential, helical order in the Ranunculaceae (Ren et al, 2010 ), the main target of the present paper, and in several other families such as the Caryophyllaceae (Lyndon, 1978 ) and the Oleaceae (Dadpour et al, 2011 ). These species exhibit considerable variation in floral organ numbers, as we will show.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…The floral organ numbers are determined during the initiation and fate determination of the floral organs. Scanning electron microscopic studies of the initiations of floral organs revealed that the sepal primordia initiate in sequential, helical order in the Ranunculaceae (Ren et al, 2010 ), the main target of the present paper, and in several other families such as the Caryophyllaceae (Lyndon, 1978 ) and the Oleaceae (Dadpour et al, 2011 ). These species exhibit considerable variation in floral organ numbers, as we will show.…”
Section: Introductionmentioning
confidence: 70%
“…arbor-tristis , whereas J . fruticans shows pentamerous helical initiation but stochastically develops four or six sepals (Sehr and Weber, 2009 ; Dadpour et al, 2011 ). Thus, there are three patterns of Oleaceae sepal initiation: the simultaneous initiation of four sepals, the extra two sepals (4 + 2) found in N .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past the variation in seed morphology has been used variously in plant systematics ranging from identification (Sako et al 2001, Khalik andVan der Maesen 2002) and taxonomic circumscription (Constantinidis et al 2001, Mendum et al 2001, Amini et al 2011, Sadeghian et al 2014, Ghimire et al 2015a, 2016a, Arabi et al 2017) to phylogenetic inference (Hufford 1997, Arambarri 2000 and character-state evolution (Fukuhara 1999, Simons andHedin 1999). Although quite a few embryological, floral, and carpological studies of Oleaceae have been carried out (Rohwer 1993, 1994, Sher and Weber 2009, Dadpour et al 2011, Naghiloo et al 2013, Ghimire and Heo 2014, Ghimire et al 2015b, studies on comparative seed morphology and seed coat anatomy are still scarce for the family. Therefore, it is necessary to undertake an extensive investigation of the seed morphology and anatomy of the Oleaceae to evaluate their applicability to the tribal and subtribal taxonomy.…”
Section: Introductionmentioning
confidence: 99%